Psychiatric rehabilitation in schizophrenia – a review of chosen methods - Fijałkowska, Paula; Lewczuk, Edward; Pawłowska, Beata (Current Problems of Psychiatry, 2012)
The aim of this article is to present different types of rehabilitation techniques aimed at patients with diagnosed schizophre-nia. People with mental disorders experience numerous problems both as individuals and as members of society and social support programmes are meant to counteract their social exclusion. The article presents such forms of help as Psychiatric Day-Care Units and Psychiatric Rehabilitation Wards, which offer skills training, psychoeducation, physical rehabilitation and therapeutic camps. The article stresses the importance of work, which allows individuals to integrate into the society and is an effective therapeutic tool. Vocational rehabilitation can be provided by therapy workshops and, later on in the process, by institutions of vocational activity, which offer career counseling. The perception of people with mental disorders has changed as a result of a social campaign run in Poland, called ‘Open the Doors – Schizophrenia’.